Cardiorespiratory Fitness 2020
DOI: 10.5772/intechopen.83586
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Lifestyle and Body Composition among Young Females in Serbia of 18–29 Years of Age

Abstract: The aim of this study is to determine if certain lifestyle and habits influence the characteristics of body composition among young females in Serbia. The research included 248 randomly chosen females between 18 and 29 years of age. Data about physical activity were collected via validated questionnaire. In determining body composition, we relied on the instrument InBody 720, which enabled us to define the variables: body height (BH), body weight (BW), body fat mass percentage (BFM%), skeletal muscle mass perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, it was observed that the age, time spent in service, shift work, career progression, and high levels of occupational stress have been factors that promote negative changes in body composition and BMI of police officers (Boyce et al, 2008;Gu et al, 2012;Kukić et al, 2017;Sorensen et al, 2000;Violanti et al, 2009). Occupational sitting coupled with aging was shown to be related to detrimental changes in lifestyle (Ćopić, Đordjević-Nikić, Rakić, Maksimović, & Dopsaj, 2019;Dimitrijević, Vuković, Ćopić, & Dopsaj, 2012). This may predispose them to greater risk of obesity and associated morbidities (Charles et al, 2008;Dopsaj & Vuković, 2015;Violanti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was observed that the age, time spent in service, shift work, career progression, and high levels of occupational stress have been factors that promote negative changes in body composition and BMI of police officers (Boyce et al, 2008;Gu et al, 2012;Kukić et al, 2017;Sorensen et al, 2000;Violanti et al, 2009). Occupational sitting coupled with aging was shown to be related to detrimental changes in lifestyle (Ćopić, Đordjević-Nikić, Rakić, Maksimović, & Dopsaj, 2019;Dimitrijević, Vuković, Ćopić, & Dopsaj, 2012). This may predispose them to greater risk of obesity and associated morbidities (Charles et al, 2008;Dopsaj & Vuković, 2015;Violanti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%